Drug Addiction: A Psychological Study: Understanding the causes, treatment, and prevention of drug addiction (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Drug addiction has become a worldwide problem and the leading cause of death. The global problem of addiction and drug abuse is responsible for millions of deaths and millions of new cases of HIV every year. In recent years, India is seeing a rising trend in drug addiction. The most common use of drug in India is alcohol, followed by cannabis and opiates. Drug use, whether licit or illicit, causes serious health problems in individuals. The National level survey conducted on drug use in India indicated that prevalence of drug abuse among males in the general population is significant. Drug abuse among women exists. Despite the fact that more men use drugs than women, the impact of drug use tends to be greater on women, because women lack access to care for drug dependence. Economic burden, disturbed family environment, violence, and psychological problems are other consequences of drug abuse in the family. Adolescent drug abuse is another major area of concern because more than half of the person’s with substance use disorder are introduced to drugs before the age of 15 years. At present, there exists a significant gap in service delivery. The current paper highlights the causes of drug abuse, and describes the treatment and prevention of drug abuse and addiction for proper management of the problem.